Chemical and enzymatic synthesis of Aureocin A53 peptide conjugates - Yip, Rayna Weiqin (Nanyang Technological University, 2023)
Aureocin A53 (AucA) is a bacteriocin holding great potential as a drug to combat antimicrobial resistance. Displaying activity against multidrug-resistant staphylococcal strains, AucA penetrates non-specifically to the cytoplasmic membrane, resulting in lysis. Here, the use of microwave-assisted solid phase peptide synthesis (SPPS) to produce AucA was documented for the first time. Additionally, two AucA peptide conjugates were synthesized by enzymatic and chemical means. The lipopeptide contained the covalent attachment of myristic acid to the N-terminal amine of AucA, while the glycopeptide contained the covalent attachment of maltose to the C-terminal hydrazide of the N-acetylated peptide. Circular dichroism (CD) spectra detected the presence of ⍺-helical structures for all peptides and peptide conjugates. Minimum inhibitory concentration (MIC) assay revealed the ability of native AucA to target S. aureus at micromolar concentrations, with a MIC value of 6.25 µg/mL. However, both peptide conjugates displayed lowered antimicrobial activities than native AucA, likely due to steric hindrance and N-acetylation of the lipopeptide (MIC >100 µg/mL) and glycopeptide (MIC 12.5 µg/mL), respectively. In terms of proteolytic stability against trypsin endopeptidase, a near-complete degradation was observed for the lipopeptide, while N-acetylation was postulated to enhance the proteolytic stability of AucA, with no further enhancement after maltose attachment.